Rola krajoznawstwa i turystyki w integracji wiedzy z literatury z innymi dyscyplinami naukowymi = The role of sightseeing and tourism in the integration of knowledge from literature with other scientific disciplines - Denek, Kazimierz (1932-2016) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Tourism and country sightseeing contain in themselves considerable possibilities of educatonally genune and real influence on adolescents. They play an essential role in the development of appropriate personalities in young people, in the formation of their attitudes in meeting their needs and in preparing the young generation to fullfil ist socially important roles as well as to perform ist various life tasks.
Keywords: krajoznawstwo; turystyka; literaturoznawstwo